2018
DOI: 10.1002/ldr.2917
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting sediment sources in a large agricultural catchment under no‐tillage in Southern Brazil (Conceição River)

Abstract: Brazil is a leader in the adoption of conservation agriculture practices and technologies. However, the impact of these practices on sediment sources at the catchment scale has not been quantified yet, particularly in grain growing regions, where a conservationist no‐tillage system is implemented to protect soils. To address this knowledge gap, a sediment fingerprinting study based on elemental geochemistry was carried out in a large agricultural catchment (804 km2) of Southern Brazil where no‐tillage practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 52 publications
(73 reference statements)
4
37
1
Order By: Relevance
“…Agriculture and livestock rearing are the main economic activities, while urban areas occupy only 0.6% of the area. [32] The presence of anthropogenic markers was monitored in four sub-watersheds of the Guapor e River watershed named Capingui, Marau, Lajeado Carazinho, and Carazinho (Figure 1).…”
Section: Guapor E Watershed and Sampled Sitesmentioning
confidence: 99%
“…Agriculture and livestock rearing are the main economic activities, while urban areas occupy only 0.6% of the area. [32] The presence of anthropogenic markers was monitored in four sub-watersheds of the Guapor e River watershed named Capingui, Marau, Lajeado Carazinho, and Carazinho (Figure 1).…”
Section: Guapor E Watershed and Sampled Sitesmentioning
confidence: 99%
“…In the Guaporé catchment, overbank sediment deposition may be observed in the vicinity of the river system in the upper catchment area. Previous findings indicated that cropland (88 ± 19%) was the main source of outlet sediment, compared with very low channel bank contributions (10 ± 18%) (Tiecher, ). As the sediment supply from channel banks is negligible in this catchment, the discussion will focus on the variations of cropland contributions to sediment transport in this catchment.…”
Section: Discussionmentioning
confidence: 97%
“…In this current study, sediment sources are investigated in the agricultural Guaporé catchment (Rio Grande do Sul, Brazil) where croplands were modelled to dominate the sediment supply (88 ± 19%) (Tiecher, ). Contrasting farming practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sediment fingerprinting approach has attracted expanding interest driven by increasing recognition of the environmental significance of fine-grained sediment and the urgent need to target management measures, and this is reflected by a rapid growth in the number of scientific publications (Koiter et al, 2013;Walling, 2013). The growing body of literature focuses on either methodological assessment and refinement by testing critical assumptions (e.g., source classification, fingerprint property behavior, uncertainty, mixing model optimization), or reports case study applications in various environments for scientific and management (e.g., identifying critical source for targeting control measures, re-evaluating managed sites and assessing conservation efficacy) purposes (Tiecher et al, 2018).…”
Section: A Brief Review Of the Science Of Sediment Source Fingerprintmentioning
confidence: 99%